ScrumGame: A Serious Game to Initiate Software Trainees in Scrum - Rodríguez, Guillermo Horacio (2020)
Serious games have emerged to improve the commitment and performance of users, since they accomplish a specific goal, integrating with the mechanics of the game, thus creating a very attractive mission. The use of serious games in Software Engineering to increase developer engagement has been investigated with great interest to train future professionals to experience situations that they might face in software development. This work presents ScrumGame, a serious game to train both Software Engineering students and software practitioners in Scrum. The game was assessed through pre-test-post-test design with 10 users who use Scrum in their daily work. For this, the SIMS and MSLQ tests were used, which both were completed by the users before and after playing the game. We aimed to measure how the use of the game impacts on learning strategies and motivation. Backed up with statistical significance support, results show that ScrumGame generated a positive impact on the users, indicating an increase in the variables studied, key issues in the development of self-managed education.